Histone-acetylation: a link between Alzheimer's disease and post-traumatic stress disorder? - Bahari-Javan, Sanaz; Sananbenesi, Farahnaz; Fischer, Andre (Frontiers in Neuroscience, 2014)
The orchestration of gene-expression programs is essential for cellular homeostasis. Epigenetic processes provide to the cell a lkey mechanism that allows the regulation of gene-expression networks in response to environmental stimuli. Recently epigenetic mechanisms such as histone-modifications have been implicated with cognitive function and altered epigenome plasticity has been linked to the pathogenesis of neurodegenerative and neuropsychiatric diseases. Thus, key regulators of epigenetic gene-expression have emerged as novel drug targets for brain diseases. Numerous recent review articles discuss in detail the current findings of epigenetic processes in brain diseases. T he aim of this article is not to give yet another comprehensive overview of the field but to specifically address the question why the same epigenetic therapies that target histone-acetylation may be suitable to treat seemingly different diseases such as Alzheimer’s disease post-traumatic stress disorder.